Achieving Clean Water: A Simple Filtration Approach for Managing River Water - Humairo, Mika Vernicia; Kriscahyanti, Sila; Yuniarfika, Azizah; Tristan, Muhammad; Amadia, Shiesil Rizqia; Famiyah, Neila Rizqi; Mokhtar, Siti Aisah Binti (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2026)
Bango River is one of river in Malang city with its role as a primary source for irrigation and community sanitation. According to data from Indonesian Ministry of Environment and Forestry, it was found that the river suffered from heavy pollution for five consecutive years because of open defecation practices and high sediment loads. This condition creates a critical gap between existing water quality and the hygiene standards required for public health. This study aims to make a filtration for Bango water, so people can use it as their function. This filtration system improved the physical and chemical parameters of Bango River water so can suit with national water sanitation standards. This research used the method of pre and post-test experiments to treat Bango River water using simple filtration. The results were analyzed based on Indonesian Ministry of Health Regulation No 2 of 2023. The results showed a significant increase in the quality of physical and chemical parameters such as turbidity, TDS, and DO in Bango River water. Therefore, it can be concluded that the simple filtration device is effective in reducing three out of five water quality parameters that were tested